Comparison between subjective and quantitative methods for assessing the resolution limit of radiographic systems - Alvarez, Matheus [UNESP]; Oliveira, Marcela de [UNESP]; Pina, Diana Rodrigues de [UNESP]; Miranda, José Ricardo de Arruda [UNESP] (My University, 2012)
The aim of this study was to compare two ways of measuring the resolution limit of radiographic systems, one subjective and one quantitative. To this end, nine images were acquired with different radiographic techniques using a pattern of bars and aluminum plates. With these images were acquired modulation transfer function (MTF) through the edge image obtained by the aluminum plate — the MTF 10% was measured on all images — and the variation of these points, which was faced with the evaluation obtained by the resolution limit of the standard bar. Although we have observed a greater variation between measurements obtained using the bar-pattern, the simplicity of this measuring technique favors the common use of the same. We concluded that, to optimize the quality control of radiographic equipment, it is suggested to measure the MTF at least in periods of time while the annual pattern of bars to be used in shorter time periods to measure changes in resolution of the system.

O objetivo deste estudo foi comparar duas formas de aferição da resolução limite de sistemas radiográficos, uma subjetiva e outra quantitativa. Para tal, foram adquiridas nove imagens com diferentes técnicas radiográficas utilizando um padrão de barras e placas de alumínio. Com estas imagens, foram adquiridas a função de transferência modulada (FTM) através da imagem da borda obtida pela placa de alumínio — a FTM foi aferida 10% em todas as imagens — e a variação destes pontos — que foi confrontada com a avaliação da resolução limite obtida através do padrão de barras. Apesar de termos observado uma maior variação entre as medidas obtidas com a utilização do padrão de barras, a simplicidade de medição desta técnica favorece o uso corriqueiro da mesma. Concluí-se que, visando a otimização do controle de qualidade de equipamentos radiográficos, sugere-se fazer a medição da FTM pelo menos em períodos de tempo anuais, enquanto que o padrão de barras seja utilizado em períodos de tempo menores para a aferição de mudanças na resolução do sistema.
Comparação entre métodos subjetivos e quantitativos na medida da resolução limite de sistemas radiográficos
Keywords: Optimization; Quality control; Radiography; Otimização; Controle de qualidade; Radiografia